Integrating art into science education: a survey of science teachers' practices. Issue 10 (3rd July 2017) - Turkka, Jaakko; Haatainen, Outi; Aksela, Maija
ABSTRACT: Numerous case studies suggest that integrating art and science education could engage students with creative projects and encourage students to express science in multitude of ways. However, little is known about art integration practices in everyday science teaching. With a qualitative e-survey, this study explores the art integration of science teachers ( n = 66). A pedagogical model for science teachers' art integration emerged from a qualitative content analysis conducted on examples of art integration. In the model, art integration is characterised as integration through content and activities. Whilst the links in the content were facilitated either directly between concepts and ideas or indirectly through themes or artefacts, the integration through activity often connected an activity in one domain and a concept, idea or artefact in the other domain with the exception of some activities that could belong to both domains. Moreover, the examples of art integration in everyday classroom did not include expression of emotions often associated with art. In addition, quantitative part of the survey confirmed that integration is infrequent in all mapped areas. The findings of this study have implications for science teacher education that should offer opportunities for more consistent art integration.